Designing Onboarding Together: Insights from Human Resources Focus Group - Sasseron, Bethânia Monteforte (Global journal of Business and Integral Security, 2026)
This study investigates HR professionals’ perspectives on designing a global onboarding programme in a complex, multi-site humanitarian organisation. Using a qualitative focus-group framework, five online sessions (n = 32) were conducted between July–October 2022 via Microsoft Teams and Miro to co-create onboarding requirements grounded in practitioner insight. Reflexive thematic analysis identified six domains: Social Inclusion, Onboarding Monitoring, Practices during Onboarding, Learning and Development, Onboarding Steps, and Organisational Culture, which informed a co-designed, four-phase model (Preparation; Social Inclusion; Learning and Development; Technical Role-Specific Training). Findings indicate that HR stakeholders conceptualise onboarding as a strategic, human-centred capability that requires standardised yet context-sensitive structures, digital artefacts, and participatory governance. Digital collaboration enabled global engagement, auditable outputs, and transparent design processes aligned with organisational values and sustainability goals. The study advances onboarding scholarship by centring HR practitioner voices and demonstrating how digitally enabled focus groups can produce actionable frameworks for cross-border contexts. Methodologically, it contributes to online qualitative practice; practically, it offers a replicable onboarding architecture for dispersed, mission-driven organisations.